2008
DOI: 10.1007/s00299-008-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a SERK-like gene in coconut and analysis of its expression during the formation of embryogenic callus and somatic embryos

Abstract: Somatic embryogenesis involves different molecular events including differential gene expression and various signal transduction pathways. One of the genes identified in early somatic embryogenesis is S OMATIC E MBRYOGENESIS R ECEPTOR-like K INASE (SERK). Cocos nucifera (L.) is one of the most recalcitrant species for in vitro regeneration, achieved so far only through somatic embryogenesis, although just a few embryos could be obtained from a single explant. In order to increase efficiency of this process we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 20 publications
10
59
0
2
Order By: Relevance
“…StSERK1 was upregulated during the induction of somatic embryogenesis in potato and was continuously repressed during the embryo-transition phase (Sharma et al, 2008). CnSERK was detected in embryogenic tissues during somatic embryo-genesis, with expression greatly decreasing during somatic embryo development (Pérez-Núñez et al, 2009). When wounded explants were cultured in our PLB induction medium, PhSERK5 was highly expressed during the third week, when secondary PLBs became apparent (Figures 1 and 5).…”
Section: Discussionmentioning
confidence: 95%
“…StSERK1 was upregulated during the induction of somatic embryogenesis in potato and was continuously repressed during the embryo-transition phase (Sharma et al, 2008). CnSERK was detected in embryogenic tissues during somatic embryo-genesis, with expression greatly decreasing during somatic embryo development (Pérez-Núñez et al, 2009). When wounded explants were cultured in our PLB induction medium, PhSERK5 was highly expressed during the third week, when secondary PLBs became apparent (Figures 1 and 5).…”
Section: Discussionmentioning
confidence: 95%
“…In several species, SERK expression has been linked to acquisition of embryogenic competence Thomas et al, 2004;Pérez-Núñez et al, 2009;Cueva et al, 2012;Talapatra et al, 2014). Monitoring of expression during somatic embryogenesis in in vitro cultures revealed that CaSERK was most strongly expressed in embryogenic callus.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of SERK proteins in regulating somatic embryogenesis was first described for DcSERK in embryogenic cell suspension cultures of carrot more than 15 years ago (Schmidt et al, 1997). Since then SERK gene homologs have been identified and their role in mediating somatic embryogenesis demonstrated in several monocot and dicot species such as Arabidopsis thaliana , Medicago truncatula (Nolan et al, 2003), Triticum aestivum (Singla et al, 2008), Vitis vinifera (Maillot et al, 2009), Cocos nucifera (Pérez-Núñez et al, 2009), Ananas comosus (Ma et al, 2012) and Cyrtochilum loxense (Cueva et al, 2012). Moreover, a gymnosperm SERK homolog has recently been discovered and its association with somatic embryogenesis was shown (Steiner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…By following the expression of particular genes during the embryogenesis process, the early selection of the appropriate cell culture lines most likely to undergo SE can be achieved. A range of marker genes have been discovered, including CnSERK, CnANT, CnCDKA [84][85][86] that can indicate those cell culture lines that are most likely to undergo SE. In addition, DNA-based markers can also be used to assess the extent of somaclonal variation within the SE-derived plantlets using Random Amplification of Polymorphic DNA (RAPD), Simple Sequence Repeats (SSR) or Amplified Fragment Length Polymorphism (AFLP) analysis.…”
Section: Somatic Embryogenesismentioning
confidence: 99%